Building energy management system in smart grid - Nang Hom Nuon Nuon (2015)
World energy demand is increasing remarkably as a consequence of population growth, economic growth and fast-paced technology innovations. In order to overcome energy crisis, people are reaching out for reliable and sustainable form of renewable energy resources. Solar energy is one of the renewable energy. Commercial buildings are the main energy consumers and the demand is very high during office hours. Commercial buildings play a big role in managing energy usage properly in order to delay of building new generation plant. Therefore, building energy management system (BEMS) software is implemented to manage and monitor the energy consumption. Another way to reduce demand is to install solar panel since solar energy can harvest the most during day time. Hence the aim of this project is to integrate solar panel into the existing BEMS. In this report, modelling and simulation of solar cell output characteristics is presented. The simulation is done by LabVIEW programming. The simulation results verify the nonlinear output characteristic of silicon solar cell. The cost-benefit analysis is also evaluated in order to prove the feasibility of solar panel installation. This report will discuss step by step development processes.